Structural Load Determination : 2018 IBC and ASCE/SEI 7-16 - Fanella, David A. (David Anthony) (McGraw-Hill Education, 2018)
Calculate structural loads in compliance with the 2018 IBC? and ASCE/SEI 7-16This practical guide shows, step by step, how to interpret and apply the load provisions contained in the 2018 IBC? and ASCE/SEI 7-16. You will learn how to accurately determine structural loads including dead loads, live loads, and environmental loads. Throughout the book, detailed design examples, unique flowcharts, and design aids illustrate the proper usage of the code within the scope of everyday practice. Coverage includes: Structural load fundamentals IBC? and ASCE 7 explanations. Load combinationsDead, live, rain, and soil lateral loads, Snow and ice loads, Wind loads. Earthquake, Flood and tsunami loads.